Pengaruh leverage pada peringkat sukuk perusahaan non keuangan yang terdaftar di PT KSEI - gryanti, Putu Indah; Putri, I Gusti Ayu Made Asri Dwija (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Bapepam-LK Regulation No. IX.C.11 states that before conducting a public offering, sukuk issued by companies must be rated in advance by a securities rating agency that is officially recognized in Indonesia. This study aims to examine the effect of leverage on the ratings of sukuk issued by non-financial companies and registered with the Indonesian Central Securities Depository in 2018 -2021. This study also uses control variables consisting of liquidity, sukuk age, sukuk collateral, firm age, and growth. The method of determining the sample in this study is by purposive sampling method. The test tool used in this study is a multiple linear regression test with the StataMP17 application. The results of this study indicate that the leverage ratio has a negative effect on the rating of the sukuk. This indicates that the proportion of the use of debt is one of the considerations for rating agencies in rating a company's sukuk. The results of this study are in line with signal theory, where high leverage will give a signal that a company has a high risk of default.